Recent progress in highly effective electrocoagulation-coupled systems for advanced wastewater treatment - Thi Kim Cuong Phu; Phi Long Nguyen; Thi Viet Bac Phung (iScience)
Summary: Electrocoagulation (EC) has been a well-known technology for wastewater treatment over the past centuries, owing to its straightforward equipment requirements and highly effective contaminant removal efficiency. This literature review emphasizes the influence of several input variables in the EC system such as electrode materials, applied current, pH, supporting electrolyte, and inner-electrode distance on effluent removal efficiency and energy consumption. Besides that, depending on the intrinsic properties of effluents, EC is recommended to hybridize with other methods such as physical-, biological-, chemical-, and electrochemical methods in order to enhance removal performance and reduce energy consumption. Subsequently, a comprehensive analysis of EC performance is presented, including power consumption, and evaluation of the synergistic effect of multiple input variables using statistical methods. Finally, this review discusses future perspectives such as the environmentally friendly utilization of post-EC treated sludges, the development of renewable energy-driven EC systems, and the challenges of EC management by artificial intelligence.